Twelve tips for medical students to establish a collaborative flashcard project. (4th May 2019) - Hart-Matyas, Michael; Taylor, Alexandra; Lee, Han Joo; Maclean, Mark A.; Hui, Amaris; Macleod, Anna
Abstract: Medical students employ various study strategies to master large amounts of information during their medical education. Digital flashcards are an interactive, self-directed study stool that may improve knowledge retention by combining the principles of active recall and spaced-repetition. They may be studied during and beyond undergraduate medical education. However, making flashcards can be an onerous task. In this article, we describe twelve tips on how to establish and maintain a collaborative digital flashcard project based on the undergraduate medical curriculum.